A conceptual framework for analysing, improving and optimising supportability of mechanical systems. (1st January 2012) - Asjad, Mohammad; Kulkarni, Makarand S.; Gandhi, O.P.
Supportability for a user is the ability of the support provider to execute all the required activities for upkeep of the system in the most effective, efficient and timely manner throughout the system's operating life. From the support provider's perspective, design, maintenance services and logistics along with appropriate contract help in delivering the required support in a profitable manner. However, from the user's point of view, apart from uninterrupted availability of the product, the life cycle cost (LCC) associated with the product is of immense importance. Hence, a tradeoff between the supportability and the corresponding LCC is to be achieved. Although a vast amount of literature is available on the subject, yet an integrated approach that considers all parameters affecting supportability and LCC in obtaining an optimal solution needs to be developed. This paper presents a framework for analysing supportability along with a proposed methodology that can help in arriving at the optimal solution.